The influence of location, product innovation, customer relationship marketing (CRM) and competitiveness on increasing sales mediated by purchasing decisions CV. Martina Taste Bakery - Yunni Rusmawati DJ; Happy Adianita; Nur Mustika Sari; Sabilar Rosyad; Emalia Nova Sustyorini (Sean Institute, 2024)
This study aims to determine the direct effect of location, product innovation, customer relationship marketing, and competitiveness on increased sales mediated by purchasing decisions cv. martina bakery flavour. This type of research is a quantitative approach with a sample of 144 respondents using a survey method by distributing questionnaires as a data collection method. The method used to analyze is SEM with Smart PLS version 3.0. the test used is the auter model test, inner mode test, and mediation. The results of this study indicate that location variables (X1), product innovation (X2), customer relationship marketing (X3), have a positive and significant effect on increasing sales (Y). Meanwhile, competitiveness (X4) has a negative and significant effect on increasing sales. It can also be concluded that location variables (X1), product innovation (X2), customer relationship marketing (X3), and competitiveness (X4) have a positive and significant impact on purchasing decisions (Z). The relationship between the increase in sales variable (Y) has an effect. positive and significant to customer satisfaction (Z). In the mediation test the location variable (X1) product innovation (X2) customer relationship marketing (X3) to increased sales is mediated by the purchase decision is said to be partial mediation. Variable (X2) and. Competitiveness variable (X4) to increased sales mediated by purchasing decisions is said to be Full Mediation.